A Global Network Meta-Analysis of the Promotion of Crop Growth, Yield, and Quality by Bioeffectors - Herrmann, Michelle Natalie; Wang, Yuan; Hartung, Jens; Hartmann, Tobias; Zhang, Wei; Nkebiwe, Peteh Mehdi; Chen, Xinping; Müller, Torsten; Yang, Huaiyu (Frontiers in Plant Science, 2022)
Bioeffector (BE) application is emerging as a strategy for achieving sustainable agricultural practices worldwide. However, the effect of BE on crop growth and quality are still controversial and there is still no adequate impact assessment that determines factors on the efficiency of BE application. We therefore carried out a network meta-analysis on the effect of BEs using 1791 global observations from 186 studies to summarize influencing factors and the impact of BEs on crop growth, quality and nutrient contents. The results show that BEs did not only improve plant growth by around 25% and yield by 30%, but also enhanced crop quality, e.g. protein (55% increase) and soluble solids content (75% increase) as well as aboveground nitrogen (N) and phosphate (P) content by 28% and 40%, respectively. The comparisons among BE types demonstrated that especially non-microbial products such as extracts, and humic/amino acids have the potential to increase biomass growth by 40-60% and aboveground P content by 54-110%. The soil pH strongly influenced the efficiency of the applied BE with highest effects in acidic soils. Our results showed that BEs are most suitable for promoting the quality of legumes and increasing the yield of fruits, herbs and legumes. We illustrate that it is crucial to optimize the application of BEs with respect to the right application time and technique (e.g. placement, foliar). Our results provide an important basis for future research on the mechanisms underlying crop improvement by the application of BEs and on the development of new BE products.